What Do I Get For My ACE Dues? - William E. Carnahan (Journal of Applied Communications, 1987)
At the 1982 ACE meeting in Biloxi, Mississippi, it was voted to raise annual dues from $25 to $45. At that time, it was estimated that each member was costing ACE about $34 in services. There was some discussion about raising the dues to $50, but it was felt doubling the dues would be too much.